VALUASI TINGKAT KESEHATAN PADA KOPERASI KREDIT BINTANG TIMUR JAWA TIMUR MENGGUNAKAN CAMEL - Dewi Mayasari; Endah Masrunik; Anam Miftakhul Huda; Diana Elvianita (Universitas Islam Negeri Alauddin Makassar, 2018)
This research aims to level of Credit Union Bintang Timur health by using CAMEL method during a period of time of 2017. CAMEL method has five aspects, which are Capital Adequacy Ratio (CAR), earning asset quality ratio (KAP), management, asset earning power and liquidity loan to deposit ratio. The results and discussion of all CAMEL factors in the category